Gender Roles and Territorial Governance in Highland Andean Areas as Key knowledge to Biodiversity Conservation: The Case of San Pedro de Churco, Peru - Medina Canzio, Susan Mery (2025)
Gender relations within highland Andean communities reveal intricate dynamics in which hierarchical and patriarchal structures coexist alongside evolving socio-economic, cultural, and resistance-driven processes, often led by women. This study explores by first time the gendered roles and interactions in the rural settlement of San Pedro de Churco, located adjacent to the Pampa Hermosa National Sanctuary in central Peru. Employing a methodology of surveys and participant observation, the research investigates how gender dynamics manifest across domestic, healthcare, productive, and social spheres. The findings highlight ongoing transformations, particularly the emerging involvement of young women in territorial governance and local initiatives aimed at sustainable development. The study argues for the integration of a gender-sensitive perspective in environmental conservation and territory policies, as well as in rural planning for sustainable agriculture and livestock practices. Recognising women as key agents of social change is essential to fostering inclusive and sustainable futures within Andean rural contexts.